Identifying and prioritizing the advantages of implementing blockchain technology in public-private enterprises - Forozandeh, Mohammad (Annals of Management and Organization Research, 2025)
Purpose: Identifying and prioritizing the benefits of implementing blockchain technology in public-private enterprises. Research Methodology: A comprehensive literature review on this topic revealed a variety of benefits associated with the implementation of blockchain technology. These identified benefits were then presented to experts for prioritization through the use of the DEMATEL questionnaire, leading to the development of the DANP decision matrix. Results: The benefits were systematically ranked, resulting in the prioritization of tracking, security, and sustainability. Regarding the importance of the identified benefits, the experts ranked "Improving the Quantity and Quality of Services" as the most important and highest-priority benefit of implementing blockchain technology. Conclusions: Implementing blockchain technology has many important benefits for public-private companies. Limitations: Due to the research timeframe and limited interactions, only a few organizations and a medium number of personnel were examined. Contribution: Recommendations are provided for the effective application of blockchain technology to managers of public-private enterprises. This research offers valuable insights into the key benefits and priorities for implementing blockchain technology in state-owned companies. These findings can inform strategic decision-making and guide the effective adoption of this transformative technology.